Personal Branding Calon Legislatif Generasi Z Melalui Instagram: Studi Deskriptif Kualitatif Pada Akun @muhammadshoma - Royani, Shofia Fazza; Rusdiana, Joni (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2023)
Social media is an effective place to build personal branding. Personal branding through social media is used by a generation Z politician who has just entered politics. Personal branding that is carried out will affect people's perception of him and build a positive image. This research uses McNally & Speak's personal branding theory, namely distinctiveness, relevance, and consistency. Researchers examined the personal branding built by Muhammad Shoma through Instagram social media to find out how he built personal branding as a generation Z politician who had just entered politics. This is so that Muhammad Shoma can be elected to the council in the area where he lives. In this study, researchers used a descriptive qualitative approach method in order to describe the results of the study. Data was collected by direct interview techniques with Muhammad Shoma and observing posts on his Instagram. The results of this study show that the use of Instagram social media can build a positive image of Muhammad Shoma as evidenced by several posts that show him approaching the community. Such as holding studies with mothers, holding free examinations on stunting, releasing fish fry into rivers with residents, and so on. Not only that, this generation Z also likes to read and write so that he is broad-minded and critical. This is evidenced by posts of written works shared on several blog platforms and online publications. He also built personal branding by having a characteristic that he has, namely in appearance he appeared in cocoa clothes and a peci at every campaign activity even though he came from the nationalist party PDI Perjuangan.